2004
DOI: 10.1111/j.1365-2605.2004.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on sperm plasma membrane integrity and DNA fragmentation

Abstract: Cigarette smoking is a serious health problem of our society. It is known that cigarette smoke is a cell mutagen and carcinogen, and that it may affect adversely male fertility. The possible detrimental effects on sperm cells are of great interest but the data available to support this statement are somewhat elusive. To approach this problem we examined conventional semen parameters, plasma membrane translocation of phosphatidylserine (PS) (annexin V/6-CFDA cell staining) and sperm DNA integrity (comet assay) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 30 publications
1
28
1
4
Order By: Relevance
“…Belcheva and colleagues found an increased frequency of double-and single-stranded DNA breaks in spermatozoa of smokers compared with non-smokers, however, this difference did not reach statistical significance. Although the reported sperm DNA integrity of healthy smokers was within the normal range, a clear negative trend is observed (18). A recent study by Fariello and colleagues showed a decreased sperm DNA integrity and mitochondrial activity, whereas lipid peroxidation increased in male smokers with varicocele.…”
Section: In Vitro Effects Of Increasing Nicotine Concentrations On mentioning
confidence: 98%
See 1 more Smart Citation
“…Belcheva and colleagues found an increased frequency of double-and single-stranded DNA breaks in spermatozoa of smokers compared with non-smokers, however, this difference did not reach statistical significance. Although the reported sperm DNA integrity of healthy smokers was within the normal range, a clear negative trend is observed (18). A recent study by Fariello and colleagues showed a decreased sperm DNA integrity and mitochondrial activity, whereas lipid peroxidation increased in male smokers with varicocele.…”
Section: In Vitro Effects Of Increasing Nicotine Concentrations On mentioning
confidence: 98%
“…Altogether, these effects suggests that high concentrations of nicotine decrease sperm viability because this alkaloid causes PS extemalization and damages the sperm membrane. A study on men has shown an elevated PS extemalization on the sperm plasma membrane (assayed by annexin V positive staining) and a significant increase of apoptotic spermatozoa in the ejaculates of smokers (18).…”
Section: In Vitro Effects Of Increasing Nicotine Concentrations On mentioning
confidence: 99%
“…Zweitens weisen einige Studien ebenfalls auf einen Einfluss des Tabakkonsums hin (Künzle et al, 2003;Saleh et al, 2002;Wallock et al, 2001; siehe auch The Practice (Künzle et al, 2003;Vine et al, 1996;Vine et al, 1994 (Agarwal & Said, 2003;Belcheva et al, 2004;Trummer et al, 2002 (Brinkworth & Handelsman, 2000;Dallinga et al, 2002;De Rosa et al, 2003;Monsees et al, 1998;Oliva et al, 2001;Wong et al, 2003 Miller et al, 1998;Popken et al, 1999). …”
Section: Genetische Störungenunclassified
“…Despite these deleterious outcomes of CS exposure in females, cigarette smoke is well known to be reproductively toxic to males by decreasing sperm density and causing sperm abnormal morphology in smokers (Evans et al, 1981;Handelsman et al, 1984;Karagounis, Papanikolaou & Zavos, 1985;Vogt, Heller & Borelli, 1986). CS and its constituents have been documented to be associated with sperm damage such as DNA strand break (Fraga et al, 1996;Shen et al, 1997), DNA adducts (Potts et al, 1999), chromosomal abnormality (Robbins et al, 1997;Rubes et al, 1998;Yauk et al, 2007) and plasma membrane integrity (Belcheva et al, 2004). Transport in the female reproductive track (Hung et al, 2007) and sperm motility in human and model animals are also negatively aff ected when exposed to CS (Evans et al, 1981;Hung et al, 2007;Leoni et al, 2002;Polyzos et al, 2009;Ramlau-Hansen et al, 2007;Thompson & Bannigan, 2008).…”
Section: Introductionmentioning
confidence: 99%